Aplikasi Pemilihan Bibit Sapi Limosin Menggunakan Metode Weight Aggregated Sum Product Asessment (WASPAS) - Ramadhan, Muhammad Rizki; Ikhwan, Ali (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
A large and structured farming enterprise has problems with the acquisition of quality cattle, so it requires a proper decision in the process of selection of the cattle to be bred because at this initial stage will determine how much the maximum profit margin will be received in the future. At the Arifin Farm CV farm there is a problem with the selection process of the limousine cattle seed is still done manually so it will take time and great risk of selection errors because of a lot of data is not structured. This will affect the final selection result that does not match the expected qualification. In order to facilitate the selection of the cattle seed, it is necessary to build a system that covers the choice of the limousine cattle to be selected and then expanded on the farm to produce super ready-to-sale cattle. And it is also necessary to apply a method aimed at producing more accurate measurement, the method used is the method of weighted aggregated sum product assessment on the system supporting the decision selection of the limousine cattle seed, such a method is a combination of simple additive weighting and weight product method. In the application of such methods resulted in the accumulation of supporting decisions with weighted quantities and product weighted thus resulting in more accurate ranking results. Responding to the need to solve the problem, the research has produced a decision-supporting application system that can calculate the candidate limousine seed based on existing criteria and then give the results of the recommendation of the best limousine seed. The creation of such an application aims to make the selection process more structured and computerized so that the final selection will be more accurate and accountable.